Gayo Highland Takengon from 1904 To 1942: A Historical Analysis of Coffee Plantations at the Era of Dutch Colonialism (Paramita: Historical Studies Journal, 2020)
This article analyzes the history of Coffee Plantations in Gayo Highland Takengon at the time of the Dutch Colonialism era from 1904 to 1942. This historical research aimed to reveal the social and economic background, history, and the labors' condition of Gayo Highland Takengon Coffee Plantations. The historical method, which consisted of five analytical stages, was used as the method to reconstruct the history of the coffee plantations in Gayo. The findings of the research show that the geographical factors supported Gayo Highland Takengon as the area of the coffee plantation. Coffee was firstly developed at Gayo Highland by Veenhuyzen in 1908. From 1908 to 1918, coffee was a non-commercial commodity and produced on a small scale. In 1918, after the establishment of Wilhelmina Blang Gele Coffee Plantation and other plantations managed by both private and state companies, coffee increasingly became a commercial commodity. Private and state-owned companies started to employ Javanese laborers or popularly known as Jawa Kontrak and Jawa Kolonisasi. The laborers were brought in gradually from Java and bounded by the Labor System based on the Staatsblad 1911 and Staatsblad 1915. Based on these findings, it can be concluded that the geographical factors and the spirit of capitalism had driven the Dutch private and state companies to develop coffee plantations in Gayo Highland by employing the Javanese contract laborers.Tulisan ini merupakan kajian tentang analisis historis perkebunan kopi di Dataran Tinggi Gayo Takengon pada era kolonial Belanda (1904-1942). Tujuannya tidak lain untuk mengetahui faktor dibukanya perkebunan, sejarah perkebunan pertama dan buruh yang berkerja pada perkebunan kopi. Metode penelitian yang digunakan adalah metode sejarah dengan menggunakan lima tahapan. Adapun hasil penelitian menunjukkan bahwa secara geografis Dataran Tinggi Gayo cocok dijadikan sebagai kawasan perkebunan kopi, hal tersebut telah mendorong adanya penerapan kapitalisme Barat. Tanaman kopi untuk pertama kalinya dikembangkan di Dataran Tinggi Gayo pada tahun 1908, pelopor pertamamnya seorang Belanda bernama Veenhuyzen. Tanaman kopi tersebut awalnya hanya sebagai tanaman non komersial dengan jumlah terbatas, namun sejak tahun 1918 dengan dibukanya perkebunan kopi Wilhelmina Blang Gele, tanaman kopi menjadi tanaman komersial baik yang dikelola oleh Belanda maupun swasta. Buruh yang diperkerjakan pada perkebunan baik Belanda maupun swasta merupakan buruh kontak orang-orang Jawa yang disebut sebagai Jawa Kontrak dan Jawa Kolonisasi. Para buruh tersebut didatangkan dari Pulau Jawa secara bergelombang dan terikat dengan sistem kontak yang mengacu pada staatsblad tahun 1911 dan staatsblad tahun 1915.Â